Where environment and malaria intersect: Exploring the spatio-temporal footprints of Plasmodium falciparum in Tanzania - Kamaldeen Mohammed; Satveer Dhillon; Cornelius K.A. Pienaah; Isaac Luginaah; Eva-Maria Knoll; Gwyn Campbell; Herbert Hambati (PLoS ONE, 2025)
Malaria remains a public health crisis in Tanzania, with persistent morbidities and mortalities. Malaria etiology is multifactorial, with environmental factors playing a vital role in mosquito development and malaria transmission. In Tanzania and most of Sub-Saharan Africa, the Plasmodium falciparum parasite remains the most prevalent and virulent malaria parasite. Using data from the Tanzania Demographic and Health Surveys and spatio-temporal analysis, we explore the environmental determinants of P. falciparum across different regions in Tanzania over the last 2 decades. The hotspots analysis showed that the Kigoma and Kagera regions in the north-west of Tanzania as well as the Lindi and Mtwara regions in southern Tanzania were consistently hotspots of P. falciparum malaria from 2000 to 2020. Our findings also reveal and reinforce the role of environmental factors in mediating malaria epidemiology in Tanzania. Factors such as the use of insecticide-treated nets, population, evapotranspiration and aridity were often adversely associated with P. falciparum incidence. In contrast, vegetative landcover, temperature, precipitation, and the number of wet days were directly associated with P. falciparum in Tanzania. However, the relationship between these environmental factors and malaria prevalence varied temporally and spatially. Our findings further showed that, the two most important environmental factors that mediate P falciparum incidence in Tanzania over the last two decades were precipitation and aridity. Other vital predictors included the use of insecticide nets and the number of wet days. The findings provide policy pointers for targeted malaria interventions in Tanzania in the context of environmental change.